A Method for Temporal Probabilistic Reasoning - Cooper, Gregory F.; Horvitz, Eric; Heckerman, David (1988)
Temporal reasoning in complex environments often involves the interpretation of evidence under uncertainty. We have been studying the application of probabilistic reasoning techniques to the problem of temporal-data interpretation. In this report, we discuss techniques for inferring the probability of current hypothesis given temporal evidence. After reviewing the background of the problem, we present our problem-solving approach and discuss a prototype implementation.
Knowledge Systems Laboratory